Clinical efficacy and tolerance of sodium hypochlorite combined with taurine on the background of basic therapy in patients with acute pancreatitis. - Bilenkyi, G. Z.; Makarenko, O. V. (Medicni Perspektivi, 2018)
Acute pancreatitis refers to the most severe urgent diseases of the abdominal cavity. It occupies the third place after acute appendicitis and cholecystitis. The share of acute pancreatitis makes up 5-10% in the urgent pathology of the abdominal cavity organs. At the same time, in each fourth patient aseptic necrotizing pancreatitis develops, the total mortality of which even in specialized clinics of the world remains high (evidence of A, B level) range from 2.1% to 15%. Therefore, the search for new detoxifying agents with high indicators of clinical efficacy is an important trend in modern pharmacology. The purpose of this work was to establish the clinical efficacy and tolerance of the new infusion solution with the working name "Neoreodez", used against the background of basic therapy in patients with acute pancreatitis compared with the group of patients receiving baseline therapy only. A clinical study included 96 patients aged 20 to 65 years (52 men and 44 women) diagnosed with acute pancreatitis. All patients received baseline therapy (spasmolytics, proton pump inhibitors, protease inhibitors, somatostatin, antibiotics). In addition, the patients in the main group were prescribed an experimental infusion solution with the working name "Neoreodez" within 3 days. To evaluate the degree of endogenous intoxication, the method of determining the average mass molecule was used. The estimation was carried out with spectrometry in different modes of X=254 nm and X=280 nm. In addition, at the screening stage a level of malondialdehyde was determined: the latter is a clinical and laboratory marker of oxidative stress and blood pH. It was established, that the clinical efficacy of treatment in the main group of patients receiving the drug "Neoreodez" was 91.6%, which is significantly higher, than the clinical efficacy in the control group – 60.4%. Thus, the hypothesis about higher clinical efficacy of treatment in the main group of patients as compared with the control is confirmed.